High-pressure, high-temperature optical cell for mid-infrared spectroscopy. (July 2019) - Almodovar, Christopher A.; Su, Wey-Wey; Strand, Christopher L.; Sur, Ritobrata; Hanson, Ronald K.
Highlights: New optical cell design for high-pressure and high-temperature mid-infrared (up to ∼8 µm) absorption spectroscopy. Demonstrated temperature uniformity over 21.3 cm path length. Simultaneous heating and pressurization to 800 K and over 30 atm. High-resolution measurements of the nitric oxide R-branch near 5.2 µm at high gas densities indicate the presence of line mixing as well as deficiencies in the high-temperature collision broadening parameters reported in the HITEMP database. Abstract: The design, characterization, and operation of a new high-temperature, high-pressure optical cell for infrared spectroscopy is presented. The optical cell uses 16 cm CaF2 window rods to penetrate the temperature gradient between the heated optical path length and the ambient conditions surrounding the system. Along the 21.3 cm optical path length, good temperature uniformity was measured with deviations being less than 2.4% of the mean absolute temperature. Further characterization of the optical cell revealed usable transmission up to ∼ 8 µm and pressure stability from vacuum to over 30 atm. Moreover, stable operation of the optical cell during simultaneous heating and pressurization to 800 K and over 30 atm was demonstrated. To illustrate the utility of the new facility, high-resolution measurements of the R-branch in the fundamental absorption band of nitric oxide near 5.2 µm were collected at several pressures (1-34 atm) and temperatures (294–802 K) using an external cavity quantum cascade laser. The measured spectra were compared with Voigt line shape simulations using the HITRAN/HITEMP databases. At high gas densities, deviations from the Voigt line shape model are observed, emphasizing the need to further study infrared molecular spectra at high temperatures and pressures.